2 Simulation@Distance – continuing simulation training alongside social distancing guidelines. (30th November 2020) - Gumble, Eli; Broughton, Emma
Abstract : Social distancing guidelines brought about in response to the pandemic made the normal operation of a simulation centre with limited floor space impossible. To continue providing training to a greater number of candidates, methods for recreating the simulation experience with remote candidates were devised and explored: A: Conversational avatar over Zoom. Using streaming software, our pre-existing conversational avatar is presented on a Zoom call for conversational simulation with remote candidates. B: Gameplay style scenarios on CenarioVR. Candidates navigate a clinical room environment with buttons and menus to undertake a scenario. The system tracks inputs to progress the scenario. C: Remote In-Ear (RIE) coaching. Using a wireless earbud, candidates communicate remotely with centre staff ('operatives') who follow the instructions given by candidates watching a live Zoom feed. 3 variations were explored: C1: Candidates remotely watch the feed while connected to an operative by an audio call. C2: Candidates message their target operative on Zoom and text-to-speech software reads these messages to the operatives. C3: Zoom breakout rooms/separate WhatsApp video calls connect candidates to target operatives, where candidates see from the operative's perspective through a head-mounted camera. D: Virtual environments D1: Private Worlds within VRChat host scenarios. D2: GOSH's Minecraft server hosts scenarios. Proposals were scored 0–10 in: Team Interactivity, Fidelity, Range of Scenarios and Ease of Implementation. Summed total scores were: C3=32, C1=29, C2=27, A=26, B=20, D1=19, D2=10 So far, the most viable options have been trialled. Avatar use over Zoom proved easy to set up and courses using it are planned. RIE coaching's trial sessions had operatives reporting communication inefficiencies. In response, the model was revised: the wider group now coaches the whole room over Zoom. Gameplay scenarios are still under construction. Externally produced scenarios are being scrutinised. Overall, we are confident that simulation can coexist with distancing guidelines.